Epilepsy Treatment: Controlling Epileptiform Activity with Organic Electronic Ion Pumps (Adv. Mater. 20/2015). (May 2015) - Williamson, Adam; Rivnay, Jonathan; Kergoat, Loïg; Jonsson, Amanda; Inal, Sahika; Uguz, Ilke; Ferro, Marc; Ivanov, Anton; Sjöström, Theresia Arbring; Simon, Daniel T.; Berggren, Magnus; Malliaras, George G.; et al.
<x xml:space="preserve">Abstract</x> Organic electronic ion pumps (OEIPs) convert electrical current into ionic current. When in contact with neural tissue, this ionic current can be used to control the activity of neural networks. G. G. Malliaras, C. Bernard, and co‐workers develop an OEIP capable of delivering the inhibitory neurotransmitter gamma‐aminobutyric acid (GABA), as described on page 3138. The ability of the OEIP to locally suppress epileptiform activity in the mouse hippocampus is demonstrated.